2014
DOI: 10.1111/jvim.12508
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Liver Sampling Techniques in Dogs

Abstract: BackgroundThe liver sampling technique in dogs that consistently provides samples adequate for accurate histopathologic interpretation is not known.Hypothesis/ObjectivesTo compare histopathologic results of liver samples obtained by punch, cup, and 14 gauge needle to large wedge samples collected at necropsy.AnimalsSeventy dogs undergoing necropsy.MethodsProspective study. Liver specimens were obtained from the left lateral liver lobe with an 8 mm punch, a 5 mm cup, and a 14 gauge needle. After sample acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 20 publications
6
60
1
1
Order By: Relevance
“…At least 12‐15 portal triads are recommended for proper evaluation of hepatic biopsy specimens . This number of triads can be reliably achieved only if multiple needle (n > 4) or laparoscopic cup forceps biopsy specimens (n = 2‐4) are obtained . In 1 study, the diagnostic accuracy of 2 18‐gauge needle biopsy specimens was compared to a gold standard of surgical wedge biopsy of the liver in 124 patients .…”
Section: Biopsy Acquisitionmentioning
confidence: 99%
“…At least 12‐15 portal triads are recommended for proper evaluation of hepatic biopsy specimens . This number of triads can be reliably achieved only if multiple needle (n > 4) or laparoscopic cup forceps biopsy specimens (n = 2‐4) are obtained . In 1 study, the diagnostic accuracy of 2 18‐gauge needle biopsy specimens was compared to a gold standard of surgical wedge biopsy of the liver in 124 patients .…”
Section: Biopsy Acquisitionmentioning
confidence: 99%
“…Diagnostic accuracy and portal triad numbers obtained using less invasive liver biopsy sample methods have been tested. To date, the smallest sampling method that has equivalent histologic agreement (66%) with gold‐standard large wedge biopsy is the 14‐gauge (14 Ga) needle, when compared to larger sampling methods (5 mm cup and 8 mm punch biopsy instruments) . An18 Ga needle biopsy is a less accurate diagnostic method with a 49% agreement with gold‐standard wedge biopsy for the full spectrum of histologic diagnoses .…”
Section: Introductionmentioning
confidence: 99%
“…In dogs undergoing necropsy, histological diagnoses were in agreement with those from wedge samples in 66% of needle samples, 60% of cup samples, and 69% of punch samples, but these proportions were not significantly different from each other. The authors of this study concluded that the histopathologic interpretation of a liver biopsy specimen in the dog is unlikely to vary whether it contains at least 3–12 portal triads . However, it is recommended that pathologists be presented with specimens containing at least 11 portal triads .…”
Section: Diagnosis Of Hepatic Fibrosismentioning
confidence: 96%